"I Drew Myself Right There": third grade girls restorying for visual justice. Issue 4 (30th September 2021) - Wiseman, Angela M.; Turner, Jennifer D.; Cappello, Marva
Abstract : Purpose: This paper aims to present three girls' visual annotations and digital responses that restory a scene in the picturebook I'm New Here. The authors focus on how children use multimodal tools to reflect their critical knowledge of the world by illuminating how this group of girls responded to and incorporated broader social issues. Design/methodology/approach: This study takes place in a third-grade classroom. Using qualitative methods that build on critical multimodal literacy, the authors documented and analyzed children's visual and digital interpretations. Data were generated from classroom sessions that incorporated interactive readalouds, as well as students' annotated visual images, sketches, video and digital responses. The collaborative analytic process involved multiple passes to interpret visual, textual and multimodal elements. Findings: The analyses revealed how Aliyah, Tiana and Carissa used multimodal tools to engage in the process of restorying. Through their multimodal composition, they designed images that illuminated their solidarity with the young female character wearing the hijab; their desire to disrupt xenophobic bullying; and their hope for a respectful and inclusive climate in their own classroom. Originality/value: In this paper, the authors examine how three girls in a third-grade classroom restory using critical multimodal literacy methods. These girls' multimodal responses reflected how they disrupted dominant storylines of exclusionary practices. Their authentic acts of visual advocacy give us hope for the future.